Occlusal scheme in complete denture for knife-edge ridge: What works best? - Deasy Faradita Putri; Ismet Danial Nasution; Putri Welda Utami Ritonga (Indonesia Prosthodontic Association, 2026)
Fabrication of complete dentures for atrophic and knife-edge mandibular ridges poses challenges due to uneven stress distribution, which affects support, stability, and comfort. The selection of an occlusal scheme plays an important role in optimizing load transmission to the denture-supporting tissues. This systematic review aims to evaluate stress and strain distribution as well as denture displacement across various occlusal schemes in patients with atrophic or knife-edge ridges. A structured literature search was conducted through PubMed, Scopus, ScienceDirect, SpringerLink, and Google Scholar for studies published between 2015 and 2025. Seven studies met the inclusion criteria, encompassing in vitro experiments, finite element analysis (FEA), photoelastic models, and clinical evaluations. From 407 screened articles, seven studies were analyzed. Lingualized occlusion (LO) demonstrated the most even stress distribution centered along the ridge crest, while bilateral balanced occlusion (BBO) improved stability under functional loading. Monoplane occlusion (MO) reduced vertical strain but exhibited higher localized stress under specific conditions. No single occlusal scheme was universally superior. LO and MO provided favorable biomechanical outcomes in specific conditions, whereas occlusal scheme selection should be adapted to ridge morphology and patient functional needs. Keywords: complete denture, occlusal scheme, knife-edge ridge, atrophic ridge, stress distribution